The Routledge companion to Asian American and Pacific Islander literature - Lee, Rachel C. 1966- (Routledge/Taylor & Francis Group, 2014)
"The Routledge Companion to Asian American and Pacific Islander Literature offers a general introduction as well as a range of critical approaches to this important and expanding field. Divided into three sections, the volume iIntroduces "keywords" connecting the theories, themes and methodologies distinctive to Asian American Literature; addresses historical periods, geographies and literary identities; looks at different genre, form and interdisciplinarity. With 41 essays from scholars in the field this collection is a comprehensive guide to a significant area of literary study for students and teachers of Ethnic American, Asian diasporic and Pacific Islander Literature"--